Psychological Impact of Unemployment among Graduates in Tuticorin City of Tamilnadu, India - Dr. N. Maria Nevis Soris, M.Rakna (International Journal of Advanced Science and Technology, 2020)
Unemployment is the major crisis in India especially among youths who are struggle to run their family. Unemployment causes many variety of problem it affect both physical and the mental health. The purpose of this study is to investigate the psychological impact of unemployment. This study also look into both internal and the external factor of unemployment. This research is done by first hand information by framing questionnaire and distributed among 50 respondents. Descriptive research design is used in this study and convenient sampling is used. This study found out that depression, somatisation, mental illness, anxiety, poor growth of industrial policy, poor economic growth are the main psychological reason for unemployment and possible suggestion is made in the study. Keyword:. Unemployment, Psychological impact, Depression, Mental illness